TINGKAH LAKU SABAR RELEVANSINYA DENGAN KESEHATAN MENTAL - Zulhammi, Zulhammi (IAIN Padangsidimpuan, 2016)
Patient behavior is behavior that Allah commanded and selection of attitude to be auspicious. Forms can be patience in obedience to Allah, to be patient in accepting the trials of life, patient of encouragement passion of lust, invite the people to be patient in the way of Allah, to be patient in conditions of war, and to be patient in social life. The primacy of the patient, among other things for him Paradise, Allah will love him, his sins will be deleted to be canged and he may reward. Patient has relationship with mental coaching, among others: patience as mental therapy, patient as an indicator of the creation of mental health, and there is patient as a means of developing a healthy self mentally